FAKTOR YANG MEMPENGARUHI PEMANFAATAN POS PEMBINAAN TERPADU PENYAKIT TIDAK MENULAR (POSBINDU PTM) : FACTORS AFFECTING THE UTILIZATION OF INTEGRATED DEVELOPMENT POSTS OF NON-CONVERTABLE DISEASES (POSBINDU PTM) - Elis Noviati (LPPM STIKes Muhammadiyah Ciamis, 2020)
ABSTRACT The Integrated Non-Communicable Diseases Development Post (Posbindu PTM) is a form of service that involves the role of the community through promotive-preventive efforts to detect and control early risk factors for non-communicable diseases in an integrated manner. The research aims to describe the factors that influence the use of Posbindu PTM in Jalatrang Village, the Cipaku Health Center Work Area. The research method used is descriptive with a population of people aged ? 15 years. Sampling using proportional random sampling technique as many as 98 respondents. The results showed that the respondents' education was in the middle category of 52.0%, the work category of not working was 60.2%, the knowledge was in the poor category of 48.0%, the support of cadres was in the poor category of 50.0%, and the support of the family was in the category of less as much as 47.0%. Conclusion: a description of the factors that influence Posbindu PTM in general are in the poor category.